Game Theory: The Nash Equilibrium Point Identification In Bi-Matrix Games Of Economic And Social Indicators - Kreuzberg, Fernanda; Hein, Nelson; Rodrigues Junior, Moacir Manoel (Future Studies Research Journal: Trends and Strategies, 2015)
Currently companies have to think about its management system to meet not only their economic interests but also their social interests aiming at the activities’ sustainability and longevity. In this research, the goal is to identify the Nash equilibrium point in the bi-matrix game of economic and social indicators of the companies of Public Utilities sector listed on the BM & FBovespa. The research was conducted with a sample of 26 companies. To evaluate the economic performance it was used the profitability and market indicators; for evaluating the social performance, it was used the indicators derived from the VAD (Value Added Statement). In the estimation of earnings among indicators, it was used the standard parameters of the multiple linear regression. The obtained results highlighted the existence of at least one point of equilibrium for the years analyzed and, especially in the models, two points of equilibrium were proposed for 2009 and 2011 and three for 2010. It is noteworthy that, in the proposed model it was confirmed the hypothesis of the existence of at least one point of equilibrium. Thus, it was possible to meet the research objective, namely, that it is possible to meet both economic aspects and the social aspects of the companies when the indicators are taken as basic information.